Peningkatan Kesadaran Lingkungan dan Kemampuan Bahasa Inggris Masyarakat melalui Media Papan Edukasi Sampah - Daulay, Nirmala Sari; Lucyana, Lucyana; Harsya, Fadhil Al; Ganesa, Repaldi (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2026)
Environmental problems, especially waste management, remain a major issue in the community due to low environmental awareness and limited understanding of the impacts of waste. In addition, the community’s English language skills, particularly basic environmental vocabulary, are still limited. This community service program aims to improve environmental awareness and enhance the community’s English language skills through waste education board media. The waste education boards were designed as simple and visual learning media presenting types of waste, waste decomposition time, and basic English vocabulary related to environmental topics. The program was implemented through preliminary observation, installation of the education boards, and socialization activities with the community using a communicative and participatory approach. The results indicate that the use of waste education boards increased community awareness of proper waste management and environmental cleanliness. Furthermore, community members showed improved understanding of basic English vocabulary related to environmental issues. Therefore, waste education boards can be considered an effective and sustainable medium for improving environmental awareness and basic English language skills within the community.